Relationship Between Premature Rupture Of Membranes And Caesarean Section Delivery Analytical Observational Study at Sultan Agung Islamic Hospital Semarang - Nur Intan, Yulice Soraya; Sholeh, Mohammad Akbarrudin; Subiyanto, Mutiara Delia (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: Premature rupture of membranes (PROM) is a rupture of the membranes before delivery which poses a serious threat in the form of an increased risk of cesarean delivery. The risk of greater morbidity and mortality needs to be considered in cesarean delivery compared to vaginal delivery. Objective: This study aims to determine the relationship between premature rupture of membranes and delivery by cesarean section at Sultan Agung Islamic Hospital, Semarang. Methods: This research is an analytic observational study with a cross sectional research design. The population of this study was pregnant women with inpatient deliveries at the Sultan Agung Islamic Hospital, Semarang in 2018-2020. The study sample size was 50 patients. The research instrument used medical records from the Obstetrics and Gynecology section at Sultan Agung Islamic Hospital, Semarang. The sampling technique of this study is a non-probability sampling technique with purposive sampling method and meets the inclusion and exclusion criteria. Data were analyzed by Chi Square Test (X2). Results: The results of the study from a total of 50 samples obtained were 19 patients (38%) with PROM, of which 10 were delivered by cesarean section (52.6%) and 9 patients had vaginal delivery (47.4%). Patients who did not experience PROM were 31 patients (62%) of which 26 were delivered by cesarean section (83.9%) and 5 patients delivered vaginally (16.1%). The results of the Chi Square test (X2) obtained a significance value or Asymptotic Significance (2-sided) of 0.039. Conclusion: The conslusion of this study is that there is a relationship between premature rupture of membranes and delivery by cesarean section. International Journal of Human and Health Sciences Vol. 07 No. 02 Apr’23 Page: 128-132